Force Analysis of Double Pitch Point Cycloid Drive with Intermediate Rolling Elements and Free Retainer; Applied Mechanics and Materials; Vol. 756 : Mechanical Engineering, Automation and Control Systems (MEACS2014) - Efremenkov (Ephremenkov) E. A. Egor Alekseevich (Mechanical Engineering, Processing and Surface Engineereng, Metals Treatment, Equipment and Tools, 2015)
Title screen